Occipital Alpha Connectivity During Resting-State Electroencephalography in Patients With Ultra-High Risk for Psychosis and Schizophrenia - Liu, Tiantian; Zhang, Jian; Dong, Xiaonan; Li, Zhucheng; Shi, Xiaorui; Tong, Yizhou; Yang, Ruobing; Wu, Jinglong; Wang, Changming; Yan, Tianyi (Frontiers in Psychiatry, 2019)
Abnormal functional connectivity is assumed to underlie neurocognitive deficits in patients with schizophrenia. As individuals with an ultra-high risk for psychosis have neurocognitive deficits that are mainly reflected in the alpha rhythm, the identification of neural networks is essential to our understanding of the disorder. We investigated the functional connectivity of the alpha rhythm during resting state EEG as a potential biomarker of clinical risk and schizophrenia and explored correlations between cognitive functioning and clinical symptoms. The participants included 28 patients with first-episode schizophrenia (FES), 28 individuals with ultra-high risk for psychosis (UHR), and 28 healthy controls (HC). The participants underwent a structured clinical interview to assess symptoms and completed a computerized battery to assess the major domains of neurocognitive functioning. Resting state EEG was recorded for 3 minutes under eyes-closed conditions. The data were segmented into 3-second artefact-free epochs, and the functional connectivity of the alpha phase was estimated using the phase lag index (PLI), which captures the true synchronization of EEG signals. The FES and UHR groups displayed increased resting-state PLI connectivity compared with the HC group (F (2,74) = 10.804, p <0.001). Significant increases in the global efficiency, the local efficiency and the path length of networks were found in the FES and UHR groups compared with those of the HC group. SZ and UHR showed an increased degree of connectivity compared with HC. The degree of the left occipital lobe area was higher in the UHR group than that in the FES group. The hypothesis of dysconnection is confirmed. Furthermore, differences between the UHR and FES group were found, which is valuable for producing clinical significance before the onset of schizophrenia.